The application of social media for marketing strategies in pharma healthcare - Proença, Maria Helena Dias (2022)
Digital is transforming the way the world does business, and healthcare is no exception. The COVID-19 outbreak has had a significant impact on internet use and accelerated the digital transition worldwide as well as in Portugal. Social media is the fastest communication network among worldwide people. During the outbreak, the usage of social media platforms increased two times more compared with normal days. With increasing health literacy and access to technology, consumers are becoming more informed and proactive towards health issues and selfmedication, 67% of them are researching health problems and symptoms tracking and 81% conduct online research before making a purchase. This change has expanded communication from offline to the internet. Electronic word-of-mouth communication (eWOM), based on social media, brought more variables to marketing communication and became an interesting field for research considering its communication potential. Indeed, several studies have shown the ability to influence interpersonal communications on products or services in the purchase intention of consumers. As so, in recent years, some authors discussed the impact of eWOM on consumer online purchasing decisions; however, the literature is still relatively nascent regarding the Pharmaceutical Industry and the self-medication segment market of Over-the-Counter medicines (OTC). Pharmaceutical companies must be aware of this paradigm change: the patient is an indispensable and active stakeholder in the present and future of healthcare, besides the physician and the payer. Pharma marketing may be moving into a more digitalized space, but there is still room for improvement, especially when it comes to social media there is an unexploited territory for pharma marketers as most pharmaceutical companies are not yet to answer these consumers habits with an effective digital presence. The current research aims to study the application of Social Media platforms for marketing or communication purposes in pharma healthcare in Portugal.